2018
DOI: 10.1016/j.juro.2017.10.048
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Upgrading from Prostate Biopsy to Radical Prostatectomy Pathology—Does Saturation Biopsy of Index Lesion during Multiparametric Magnetic Resonance Imaging-Transrectal Ultrasound Fusion Biopsy Help?

Abstract: Our results demonstrate that saturation of the index lesion significantly decreases the risk of upgrading on radical prostatectomy by minimizing the impact of tumor heterogeneity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
50
3
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 96 publications
(62 citation statements)
references
References 26 publications
4
50
3
1
Order By: Relevance
“…Accordingly, the use of mp‐MRI should be offered before prostate biopsies with the aim of reducing GU risk in the final pathology. In a study with 208 consecutive patients, the higher number of biopsy cores taken from suspected areas in mp‐MRI were shown to significantly reduce the risk of GU . In addition, Boesen et al reported a 44% PCa detection rate in the second biopsy in patients who had a previous history of negative TRUS biopsy.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Accordingly, the use of mp‐MRI should be offered before prostate biopsies with the aim of reducing GU risk in the final pathology. In a study with 208 consecutive patients, the higher number of biopsy cores taken from suspected areas in mp‐MRI were shown to significantly reduce the risk of GU . In addition, Boesen et al reported a 44% PCa detection rate in the second biopsy in patients who had a previous history of negative TRUS biopsy.…”
Section: Discussionmentioning
confidence: 98%
“…In a study with 208 consecutive patients, the higher number of biopsy cores taken from suspected areas in mp-MRI were shown to significantly reduce the risk of GU. 23 In addition, Boesen et al 24…”
mentioning
confidence: 99%
“…26 Recently, it has been shown that in men with high risk ROI, performing a saturation biopsy of the ROI can decrease the rate and risk of Gleason grade upgrading at RP. 27 Thus, in men with heterogeneous ROI found on prebiopsy MRI, more than 2 cores of the ROI should be considered to improve cancer assessment. Lastly, the detection of clinically significant cancer using MRI is limited by the amount of cancer present.…”
Section: Discussionmentioning
confidence: 99%
“…In our study of neoadjuvant ADT plus enzalutamide, we hypothesized that mpMRI prior to surgery would assess radiographic tumor response compared with baseline imaging, while also providing biopsy targets for molecular and histologic examination of pre-treatment foci. Given the high-risk population for whom neoadjuvant intense ADT is suggested to benefit, patients on our study with larger lesions on mpMRI undergo saturation biopsy of imaging targets, to more accurately assess tumor heterogeneity 15,16 .…”
mentioning
confidence: 99%